2013
DOI: 10.1016/j.rmed.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhaler devices – From theory to practice

Abstract: This brief overview of the factors determining lung deposition of aerosols provides background information required by health care providers when instructing patients to use their prescribed inhalers. We discuss differences in the optimal inhalation manoeuvres for each type of aerosol generator and the difficulties patients face. Provision of short, clear instructions with demonstration of critical steps and checking technique during later clinical visits are necessary if these aerosolised medications are to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
115
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 52 publications
2
115
1
9
Order By: Relevance
“…Lack of cooperation in young children especially hand mouth coordination may interfere with effective inhalation therapy with MDI (13,24,25). It has been demonstrated that the most common mistakes include not exhaling before starting, not shaking the MDI and inhaling for a very short time (10,13,21,(23)(24)(25)(26)(27). Similar with other studies, common mistakes detected in our study were lack of mouth rinsing after use followed by lack of exhalation before inhaling the drug and not shaking the inhaler before use.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of cooperation in young children especially hand mouth coordination may interfere with effective inhalation therapy with MDI (13,24,25). It has been demonstrated that the most common mistakes include not exhaling before starting, not shaking the MDI and inhaling for a very short time (10,13,21,(23)(24)(25)(26)(27). Similar with other studies, common mistakes detected in our study were lack of mouth rinsing after use followed by lack of exhalation before inhaling the drug and not shaking the inhaler before use.…”
Section: Resultsmentioning
confidence: 99%
“…However, Sanchis et al [5] reinforced the fact that no drug is effective until delivery to the site of action, and regular inhaler technique monitoring and training need to be performed, irrespective of the device type used or how long the patient has been using the medication.…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that Swiss physicians almost systematically add the second layer of patient education/information reported in this survey as an anticipatory response to this perceived lack of efficiency. It has been repeatedly shown that health care providers (across all disciplines) often do not sufficiently master the inhalation technique themselves (7,11,18,19) and are not sufficiently aware of device-specific handling difficulties, even more so in an increasingly complex environment with a steadily growing inhaler diversity (11,13,(20)(21)(22). In this context, the best person to provide inhaler training should be the one with the appropriate skills, adequate time, and access to teaching resources.…”
Section: Discussionmentioning
confidence: 99%